Regulating Digital Markets in Uganda: A Comparative Analysis of the Effectiveness of Merger Control Regimes in Preventing “Killer” Acquisitions - Remmy Wahanze (Uganda Christian University, 2025)
This thesis explores the regulatory interventions aimed at preventing “killer” acquisitions in the technology sector by making a side-by-side analysis of the merger control frameworks in the European Union and the United States with the aim of influencing the regulatory framework in Uganda. Unlike traditional merger control regimes, the emergence of killer acquisitions where dominant firms acquire nascent startups with the aim of eliminating future competition, poses a significant threat to the fairness in competition in digital markets under European Union Merger Regulation referrals and the United States’ scrutiny through the Department of Justice and the Federal Trade Commission provide a blueprint for how these acquisitions can be controlled. As such, these insights are then evaluated against the newly passed Competition Act, 2024 in Uganda. This thesis concludes that at present, there are numerous gaps in Uganda’s merger control system including a non-existent notification threshold, inadequate ex-post scrutiny and structural challenges with the designated enforcement agency. It then proposes specific reforms with the objective of safeguarding digital innovation from large undertakings with monopolistic behaviours in Uganda
Undergraduate research